UPAYA MENINGKATKAN HASIL BELAJAR DALAM PEMBELAJARAN BOLA BESAR DENGAN MENGGUNAKAN METODE BLENDED LEARNING PADA SISWA SMK 2 DARUL QUR’AN JELOK BUSO TAHUN 2022 - Yudha Dava Meindirwan; Subakti; Muhsan (Yayasan Baru Haji Samsudin, 2023)
This study was aimed to know the improvement of learning outcomes in big ball games using blended learning method on the students of SMK 2 Darul Qur’an Jelok Buso. The method used in this study was Class Acion Research Mehod. This study was done in two cycles in which each cycle consisted of Planning, Action, Observation, and Reflection. The data were analyzed through descriptive method using percentage technique. The preliminary condition before the action was done showed that only 8 students passed or equals to 32%. After the first cycle, the number of passed students increased as much as 13 people or equals to 52%. Then, in the second cycle, there were 20 more students who passed or equals to 80%. Thus, blended learning method can increase students learning outcomes significantly. In conclusion, the use of blended learning method can increase the learning outcomes of SMK 2 Darul Qur’an Jelok Buso students in the year of 2022. The passing percentage of big ball games material from the preliminary condition to the first cycle was 20% and from the first to the second cycle was 28%. Therefore, the improvement of passing percentage from the preliminary condition to the second cycle was 48%.